Copper‐Catalyzed One‐Pot Synthesis of Dibenzofurans, Xanthenes, and Xanthones from Cyclic Diphenyl Iodoniums. Issue 28 (1st July 2019) - Zhu, Daqian; Li, Min; Wu, Zhouming; Du, Yongliang; Luo, Bingling; Huang, Peng; Wen, Shijun
Abstract : Oxygenation of cyclic diphenyl iodoniums (CDPIs) with varied medium‐ring sizes has been fully investigated. This practical copper‐catalyzed tandem reaction of CDPIs with water as the oxygen source enables the construction of derivatised dibenzofurans and xanthenes at moderate to good yields. Moreover, structurally important xanthones are also successfully accessed under the oxygenation conditions with additional TEMPO. Abstract : Oxygenation of cyclic diphenyl iodoniums (CDPIs) with varied medium‐ring sizes has been fully investigated. This practical copper‐catalyzed tandem reaction of CDPIs with water as the oxygen source enables the construction of derivatised dibenzofurans and xanthenes at moderate to good yields. Moreover, structurally important xanthones are also successfully accessed under the oxygenation conditions with additional TEMPO.